Adding & Subtracting Integers LESSON 1-5
ADDING INTEGERS ( +3) + (+2) = +5 ○ ○ ○ + ○ ○ = ○ ○ ○ ○ ○ ○ ○ ○ + ○ ○ = ○ ○ ○ ○ ○ “temperature is +3 and add +2 (hot) degrees, temperature gets hotter” When a number is positive, you do not have to use the (+) sign. (+3) + (+2) = 5
ADDING TWO NEGATIVE NUMBERS (- 2) + (- 1) = - 3 ● ● + ● = ● ● ● “temperature is -2 and add -1 (cold) degrees, temperature gets colder”
○ + ● cancel out to get nothing Adding +1 and -1 (+1) + (-1) = 0 ○ + ● cancel out to get nothing
ADDING POSITIVE AND NEGATIVE INTEGERS (+3) + (-4) = -1 ○ ○ ○ + ● ● ● ● = ● (+3) + (-1) = 2 ○ ○ ○ + ● = ○ ○ ○
ADDING POSITIVE AND NEGATIVE INTEGERS (-5) + (+3) = -2 ● ● ● ● ● + ○ ○ ○ = ● ● (-3) + (+4) = 1 ● ● ● + ○ ○ ○ ○ = ○
ADDING POSITIVE AND NEGATIVE INTEGERS Use temperature to see if this makes sense. OR, you may notice the following “rule”: “When adding positive and negative integers, keep the sign of the larger number and subtract.”
SUBTRACTING INTEGERS (+3) - (+2) = 1 ○ ○ ○ “temperature is +3 and take away 2 hot degrees, so temperature gets colder”
SUBTRACTING INTEGERS (- 3) - (- 1) = - 2 ● ● ● “temperature is -3 and take away 1 (cold) degrees, temperature gets warmer”
SUBTRACTING INTEGERS (+3) - (+4) = ○ ○ ○ Not enough to take away! So add a “zero”. ○ ○ ○ ○ ● Take away +4 ○ ○ ○ ○ ● Left with -1 So (+3) - (+4) = -1
SUBTRACTING INTEGERS (-4) - (+1) = -5 ● ● ● ● ● ○ (-2) - (+3) = -5 (-4) - (+1) = -5 ● ● ● ● ● ○ (-2) - (+3) = -5 ● ● ● ● ● ○ ○ ○
SUBTRACTING INTEGERS (+3) - (-2) = 5 ○ ○ ○ ○ ○ ● ● (+1) - (-3) = 4 (+3) - (-2) = 5 ○ ○ ○ ○ ○ ● ● (+1) - (-3) = 4 ○ ○ ○ ○ ●●●
SUBTRACTING INTEGERS Use temperature to see if this makes sense. OR, you may notice the following “rule”: “When subtracting positive and negative integers, add the opposite!”
YOU TRY ADD SUBTRACT 1) (+6) + (-2) 1) (7) – (2) 2) (+7) + 3 2) (+8) – (-2) 3) (-5) + (+2) 3) (-9) – (+3) 4) (-3) + (-8) 4) (-2) – (-5)
ADD SUBTRACT 1) (+6) + (-2) = 4 1) (7) – (2) = 5 2) (+7) + 3 = 10 2) (+8) – (-2) = (+8) + (+2) = 10 3) (-5) + (+2) = -3 3) (-9) – (+3) = (-9) + (-3) = - 12 4) (-3) + (-8) = -11 4) (-2) – (-5) = (-2) + (+5) = 3